Meta-analysis of risk factors for pulmonary infection after radical gastrectomy for gastric cancer - Zeng-Li CHEN; Yun-Lan JIANG; Han-Mei PENG; Hong-Mei XIE; Lu LIU; Jie LI (Yixue xinzhi zazhi)
Objective To systematically evaluate the risk factors of pulmonary infection after radical gastrectomy for gastric cancer.Method PubMed, Web of Science, Embase, CNKI, Wanfang Database, VIP database and China Biomedical Literature Database were searched from the establishment of each database to December 17, 2021. Two researchers independently screened literatures and extracted data. NOS scale was used for quality evaluation, and RevMan 5.4, Stata 15.1 softwares were used for Meta-analysis.Result A total of 23 studies with a total sample size of 10,696 were included. Meta-analysis results showed that risk factors for pulmonary infection after radical gastrectomy for gastric cancer included advanced age (OR=2.67, 95%CI: 1.90-3.74, P